Effect of Anionic Surfactant on Wettability of Shale and Its Implication on Gas Adsorption/Desorption Behavior - Abdulelah, H. (American Chemical Society, 2018)
During the fracking process in shale, an interaction occurs between shale and fracking fluid that contains a cocktail of chemicals. One of the chemicals used in fracking fluid is often surfactant, which is generally used as a viscofier. However, surfactants also have the potential of significantly influencing the wettability and thus gas desorption-key factors affecting ultimate gas recovery from shale reservoirs. Even though a few studies discussed the ability of surfactants to alter wettability in shale, the implication of that change in adsorption/desorption behavior has never been experimentally investigated beyond hypothetical inferences. In this study, the influence of the wettability change by anionic surfactant on gas adsorption/desorption behavior in shale was investigated through a series of experiments. Baseline wettability readings of two shale samples were established by measuring the contact angles (BG-1 = 22.7°, KH-1 = 35°) between a drop of pure water placed on their polished surfaces, indicating that the affinity of pure water for the BG-1 surface was greater than that for KH-1. This difference can be attributed to the higher clay content and lower total organic carbon found in BG-1 as compared to KH-1. To investigate the impact of the interaction between shale and surfactants on wettability during the fracking process, we measured the contact angles again, this time with 1 wt solution of internal olefin sulfate surfactant. The surfactant-induced wettability changes of the two shale samples were investigated by measuring the contact angles again (BG-1 = 3.5°, KH-1 = 19.2°) between a drop of surfactant solution and their polished surfaces. The effect of wettability changes on gas adsorption/desorption was then evaluated utilizing the United States bureau of mines' modified method. Experiments were conducted on the two shale samples in two ways: after pure water treatment, and after surfactant treatment. The results suggest that due to the wettability alteration of the two shale samples by IOS surfactant toward more water-wet during the treatment, the methane adsorption/desorption characteristics were influenced. In BG-1 sample, IOS solution dramatically changed its wettability to become completely water-wet. Therefore, the volume of desorbed methane dropped by nearly 54. A similar but less pronounced influence was found in the KH-1 sample, where its desorbed methane dropped by 10 because of wettability alteration toward more water-wet. These reductions in the amount of desorbed gas suggest that prior to selecting a surfactant for addition to fracking fluid, its effect on wettability and gas desorption should be investigated to optimize shale gas recovery potential. © 2018 American Chemical Society.